Raman spectroscopy for the characterization of antimicrobial photodynamic therapy against Staphylococcus epidermidis - Awad, Fathi; Wichmann, Christina; Roesch, Petra; Popp, Jürgen (Journal of Raman Spectroscopy, 2018)
The aim of this study was to investigate the use of Raman spectroscopy for characterization of antimicrobial photodynamic therapy (APDT) with methylene blue (MB) to Staphylococcus epidermidis. Results showed that APDT with MB (0.5, 1.5, and 3 μM) revealed significant reduction in the viability of the microorganism. Raman spectra from the treated microorganism seem to be affected by APDT compared with their respective controls, and the highest effect was observed when MB used at 3 μM. The results obtained in this study showed that APDT can have an effect on Raman spectra of bacteria.
CRIS-Team Scopus Importer:2023-04-20
Keywords: antimicrobial photodynamic therapy; characterization; Raman spectroscopy; staphylococcus epidermidis